Preparation of silk fibroin oligopeptide based on high-pressure micro-jet technology and application of silk fibroin oligopeptide in toothpaste
Through high-pressure microjet technology, silk fibroin proteins were treated and mineralized with hydroxyapatite, and hydroxycellulose-silicon protein oligopeptide mineralization materials were prepared for toothpaste, which solved the toxic side effects of fluoride treatment and the limited remineralization effect of hydroxyapatite, and achieved efficient anti-carious and safe preparation of toothpaste.
Patent Information
- Application Number
- CN202411970330.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The prior art The use of fluoride in dental caries treatment is prone to toxic side effects, and hydroxyapatite is used alone for enamel remineralization.
The silk fibroin in the silkworm cocoon was treated by high-pressure microjet technology, degraded into oligomeric peptides, and mineralized with hydroxyapatite to prepare hydroxycellulose-silicon oligomeric peptide mineralization material for the preparation of toothpaste.
This method significantly improves the dissolution performance and safety of toothpaste, can effectively prevent caries, improve the calcium/phosphorus molar ratio on the surface of the enamel, improve the repair effect after demineralization, and avoid the toxic side effects of fluoride.
Smart Images

Figure BDA0005219363780000211 
Figure BDA0005219363780000221 
Figure BDA0005219363780000241
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of application of natural products, and specifically relates to a preparation method of silk fibroin oligopeptide based on high-pressure microfluidization technology and its application in toothpaste, and particularly relates to a preparation method of hydroxycellulose-silk fibroin oligopeptide mineralized material based on high-pressure microfluidization technology and its application in toothpaste preparation. Background Art
[0002] Mature enamel is known for its highly mineralized properties. Its main component is inorganic minerals, the core component of which is hydroxyapatite. Hydroxyapatite molecules are orderly arranged in parallel and perpendicular to its surface in the enamel, forming a unique prismatic structure. In a healthy state, the demineralization and remineralization process of hydroxyapatite maintains a dynamic balance. However, once this balance is broken, the enamel will undergo a demineralization process, which may induce the formation of early caries.
[0003] In the clinical practice of dental caries treatment, fluoride is often used as a traditional means for the remineralization treatment of enamel caries. However, it is worth noting that excessive use of fluoride may cause toxic side effects such as dental fluorosis, skeletal fluorosis and even acute fluoride poisoning. To this end, researchers have explored an innovative early treatment method for dental caries - bionic enamel remineralization technology. The core of this method is to use hydroxyapatite materials, whose mineral composition is highly similar to that of tooth hard tissue and has excellent bioactivity and biocompatibility. When hydroxyapatite is used alone for enamel remineralization, it mainly relies on its nano-scale tiny size characteristics to fill the demineralized area. Although this method shows certain potential in promoting the remineralization of caries lesions, its remineralization effect under its single action is still relatively limited. Summary of the invention
[0004] The purpose of the present invention is to address the problems of a series of toxic side effects that are easily produced by remineralization treatment with fluoride in the prior art and the low remineralization effect of hydroxyapatite, thereby developing a toothpaste with excellent solubility, good safety and effective anti-caries effect based on silk fibroin oligopeptides obtained after oxidative degradation of silk fibroin and high-pressure microfluidization treatment, and remineralization treatment with hydroxyapatite.
[0005] To achieve the above object, the present invention is achieved by the following means:
[0006] The first aspect of the present invention provides a method for preparing a hydroxycellulose-silk fibroin oligopeptide mineralized material based on high-pressure microfluidization technology, comprising the following steps:
[0007] (1) preparing a silk fibroin solution from silkworm cocoons, and adjusting the silk fibroin concentration to 50-300 mg / mL;
[0008] (2) adding a reducing agent and continuing the reaction with stirring, and then adding an oxidizing agent to carry out an oxidative degradation reaction under stirring to obtain a silk fibroin oligopeptide intermediate solution;
[0009] (3) placing the silk fibroin oligopeptide intermediate solution in a high-pressure microfluidizer for cyclic homogenization;
[0010] (4) ultrafiltration of the product after cyclic homogenization to obtain a silk fibroin oligopeptide solution, and freeze-drying to obtain a silk fibroin oligopeptide;
[0011] (5) The silk fibroin oligopeptide obtained in step (4) is mixed with hydroxyapatite and dissolved in a saturated calcium nitrate solution, and a sodium phosphate solution is added dropwise under stirring to carry out a mineralization reaction; after the mineralization reaction is completed, the pH is adjusted to neutral, the precipitate is collected by centrifugation, and the precipitate is dried and ultrafinely ground and sieved to obtain the product.
[0012] Preferably, the silk fibroin solution in step (1) is prepared by the following steps:
[0013] (1.1) Cutting the cocoons into pieces, adding them into a sodium carbonate solution and boiling them, then soaking and washing them with water; repeating the boiling and washing process 1-5 times, and drying them to obtain degummed silk;
[0014] (1.2) dissolving the degummed silk in a lithium bromide solution, filtering to remove large particles of impurities, and then centrifuging to obtain a crude silk fibroin extract;
[0015] (1.3) The crude silk fibroin extract is transferred to a dialysis bag for dialysis; when the water level in the dialysis bag no longer changes, the dialysis bag containing the crude silk fibroin extract is placed in a polyethylene glycol solution for concentration to obtain the product.
[0016] Preferably, the concentration of the sodium carbonate solution in step (1.1) is 0.1-5.0 wt %; more preferably, the concentration of the sodium carbonate solution is 3 wt %.
[0017] Preferably, in step (1.1), the boiling time is 10-50 min, the washing time is 10-30 min, and the boiling and washing processes are repeated 2-4 times; more preferably, the boiling time is 30 min, the washing time is 20 min, and the boiling and washing processes are repeated 3 times.
[0018] Preferably, the concentration of the lithium bromide solution in step (1.2) is 5-15 mol / L, and the temperature of the lithium bromide solution is 60-90°C; more preferably, the concentration of the lithium bromide solution is 9 mol / L, and the temperature of the lithium bromide solution is 70°C.
[0019] Preferably, in step (1.2), the mass ratio of the degummed silk to the lithium bromide solution is 1:3-10; more preferably, the mass ratio of the degummed silk to the lithium bromide solution is 1:5.
[0020] Preferably, the centrifugal speed in step (1.2) is 5000-15000 rpm, and the time is 10-30 min; more preferably, the centrifugal speed is 8000 rpm, and the time is 20 min.
[0021] Preferably, the relative molecular mass retained by the dialysis bag in step (1.3) is 5-15 kDa, and the dialysis time is 1-5 d; more preferably, the relative molecular mass retained by the dialysis bag is 8 kDa, and the dialysis time is 3 d.
[0022] Preferably, the concentration of the polyethylene glycol solution in step (1.3) is 5-20%, and the concentration time is 10-30 hours; more preferably, the concentration of the polyethylene glycol solution is 15%, and the concentration time is 24 hours.
[0023] Preferably, the reducing agent in step (2) is selected from vitamin C; more preferably, the reducing agent is selected from vitamin C with a concentration of 5 mmol / L.
[0024] Preferably, the volume ratio of the reducing agent to the silk fibroin solution is 0.0005-0.003:1.
[0025] Preferably, the oxidant in step (2) is selected from hydrogen peroxide; more preferably, the oxidant is selected from hydrogen peroxide with a concentration of 5 mmol / L.
[0026] Preferably, the volume ratio of the oxidant to the silk fibroin solution is 0.001-0.01:1.
[0027] Preferably, the stirring reaction in step (2) is carried out at a temperature of 40-60°C and for a time of 20-60 min; more preferably, the stirring reaction is carried out at a temperature of 45-55°C and for a time of 40-50 min.
[0028] Preferably, the temperature of the oxidative degradation reaction in step (2) is 30-60°C, and the time is 10-60 min; more preferably, the temperature of the oxidative degradation reaction is 40-50°C, and the time is 20-40 min.
[0029] Preferably, the pressure of the circulating homogenization in step (3) is 70-120 MPa, and the number of times is 1-5 times; more preferably, the pressure of the circulating homogenization is 80-110 MPa, and the number of times is 2-4 times.
[0030] Preferably, the ultrafiltration in step (4) is as follows: the product after the reaction is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa, and the effluent is taken; then the product is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution.
[0031] Preferably, in step (5), the mass ratio of the silk fibroin oligopeptide to hydroxyapatite is 1:1-3; more preferably, the mass ratio of the silk fibroin oligopeptide to hydroxyapatite is 1:2-2.5.
[0032] Preferably, in step (5), the mass volume ratio of the silk fibroin oligopeptide to the saturated calcium nitrate solution is 0.01-0.1:1; more preferably, the mass volume ratio of the silk fibroin oligopeptide to the saturated calcium nitrate solution is 0.02-0.05:1.
[0033] It should be understood that, unless otherwise specified, the "mass-to-volume ratio" in the context of the present invention should be understood in a conventional manner in the art, that is, the ratio of the mass of the solid substance (in g) to the liquid volume (in mL). For example, when the "mass-to-volume ratio of silk fibroin oligopeptide to saturated calcium nitrate solution is 0.04:1", if the amount of silk fibroin oligopeptide added is 4 g, the amount of saturated calcium nitrate solution added is 100 mL.
[0034] Preferably, in step (5), the mass ratio of the silk fibroin oligopeptide to the sodium phosphate in the sodium phosphate solution is 0.1-1:1; more preferably, the mass ratio of the silk fibroin oligopeptide to the sodium phosphate in the sodium phosphate solution is 0.2-0.5:1.
[0035] Preferably, the temperature of the mineralization reaction in step (5) is 30-50°C, and the time is 24-120h; more preferably, the temperature of the mineralization reaction is 35-45°C, and the time is 48-96h.
[0036] The second aspect of the present invention provides a hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the above preparation method.
[0037] The third aspect of the present invention provides the use of the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the above preparation method in the preparation of toothpaste.
[0038] The fourth aspect of the present invention provides a toothpaste comprising the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the above preparation method, and auxiliary materials.
[0039] Preferably, the auxiliary materials include one or more of calcium carbonate, sorbitol, glycerin, hydrated silica, sodium saccharin, xanthan gum, sodium lauryl sulfate, cellulose gum, parabens, and water.
[0040] Preferably, the toothpaste comprises the following ingredients in percentage by mass:
[0041] 2.5-10% hydroxyapatite-silk fibroin oligopeptide mineralized material, 10-20% calcium carbonate, 10-20% sorbitol, 5-10% glycerol, 1-5% hydrated silica, 1-5% saccharin sodium, 1-3% xanthan gum, 0.5-3% sodium dodecyl sulfate, 0.5-2% cellulose gum, 0.05-0.5% p-hydroxybenzoate, and the balance is water; the total mass percentage of each component is 100%.
[0042] In the ameloblast-guided enamel biomineralization mechanism, protein components play a core role. They are closely linked to the remineralization process of hydroxyapatite, greatly enhancing the structure and mechanical properties of hydroxyapatite. The key to this process is that proteins can precisely regulate the directional growth of hydroxyapatite crystals, thus forming a unique hydroxyapatite-protein composite remineralization material. Silk fibroin is a natural polymer extracted from silk fibers with excellent biocompatibility, but its molecular weight is too large and its solubility is poor.
[0043] The present invention utilizes specific oxidative degradation and high-pressure microfluidization technology to treat silk fibroin; wherein high-pressure microfluidization is a good physical modification method, and the silk fibroin is ejected at high speed and collides with the impact ring, generating shearing, cavitation and other effects to break it. During the sample processing, the silk fibroin is simultaneously subjected to multiple mechanical forces, thereby inducing changes in its macromolecular structure and properties. By subjecting the silk fibroin to high-pressure microfluidization technology, its particle size can be significantly reduced, thereby greatly improving the solubility of the protein. This improvement greatly promotes the effective remineralization process of silk fibroin and hydroxyapatite. In addition, the mineralized material has excellent adsorption capacity, can fit closely to the surface of damaged enamel crystals, guide and arrange the enamel-like crystal layers into bundles, and effectively realize the repair and regeneration of tooth enamel.
[0044] The present invention makes full use of the advantages of excellent biocompatibility of silk fibroin, and by subjecting it to oxidative degradation, high-pressure microfluidization and other process treatments, and strictly controlling the homogenization pressure during the high-pressure microfluidization treatment, the particle size of silk fibroin oligopeptide can be greatly reduced, its solubility performance can be improved, and it helps to promote the mineralization fusion with hydroxyapatite. The toothpaste prepared by the mineralized material of the present invention can effectively reduce the degree of caries, improve the calcium / phosphorus molar ratio of the enamel surface, improve the repair effect on enamel after demineralization, and help inhibit the progress of demineralization in patients with enamel caries, and promote remineralization. In addition, the present invention uses silkworm cocoons from natural sources as the main preparation raw materials, does not add any fluorine-containing chemical components, has low cost and good safety, can effectively avoid the various toxic and side effects caused by traditional fluoride in the process of treating dental caries, and has great market prospects and social significance. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0046] Example 1
[0047] A hydroxycellulose-silk fibroin oligopeptide mineralized material based on high-pressure microfluidization technology, wherein the preparation method comprises the following steps:
[0048] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0049] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 50°C for 45 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidative degradation reaction was carried out at 45°C with stirring for 30 min to obtain a silk fibroin oligopeptide intermediate solution.
[0050] (3) The concentration of the silk fibroin oligopeptide intermediate solution was adjusted to 100 mg / mL, and the solution was placed in a high-pressure microfluidizer and subjected to cyclic homogenization treatment at 95 MPa for 3 times.
[0051] (4) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0052] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0053] Furthermore, the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 5% hydroxyapatite-silk fibroin oligopeptide mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium dodecyl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0054] Example 2
[0055] A hydroxycellulose-silk fibroin oligopeptide mineralized material based on high-pressure microfluidization technology, wherein the preparation method comprises the following steps:
[0056] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0057] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 45°C for 50 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidatively degraded at 40°C with stirring for 40 min to obtain a silk fibroin oligopeptide intermediate solution.
[0058] (3) The concentration of the silk fibroin oligopeptide intermediate solution was adjusted to 100 mg / mL, and the solution was placed in a high-pressure microfluidizer and subjected to cyclic homogenization treatment at 80 MPa for 4 times.
[0059] (4) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0060] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0061] Furthermore, the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 5% hydroxyapatite-silk fibroin oligopeptide mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium dodecyl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0062] Example 3
[0063] A hydroxycellulose-silk fibroin oligopeptide mineralized material based on high-pressure microfluidization technology, wherein the preparation method comprises the following steps:
[0064] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0065] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 55°C for 40 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidatively degraded at 50°C with stirring for 20 min to obtain a silk fibroin oligopeptide intermediate solution.
[0066] (3) The concentration of the silk fibroin oligopeptide intermediate solution was adjusted to 100 mg / mL, and the solution was placed in a high-pressure microfluidizer and subjected to cyclic homogenization treatment at 110 MPa for two times.
[0067] (4) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0068] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0069] Furthermore, the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 5% hydroxyapatite-silk fibroin oligopeptide mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium dodecyl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0070] Comparative Example 1
[0071] A mineralized material, the preparation method of which comprises the following steps:
[0072] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0073] (2) Take 1 L of silk fibroin solution, place it in a high-pressure microfluidizer, and circulate homogenization for 3 times at 95 MPa.
[0074] (3) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0075] (4) 3 g of the silk fibroin oligopeptide obtained in step (3) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0076] Furthermore, the mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 5% mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium lauryl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0077] Comparative Example 2
[0078] A mineralized material, the preparation method of which comprises the following steps:
[0079] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0080] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 50°C for 45 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidative degradation reaction was carried out at 45°C with stirring for 30 min to obtain a silk fibroin oligopeptide intermediate solution.
[0081] (3) The silk fibroin oligopeptide intermediate solution is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove macromolecular substances and the effluent is taken; then the solution is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0082] (4) 3 g of the silk fibroin oligopeptide obtained in step (3) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0083] Furthermore, the mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 5% mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium lauryl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0084] Comparative Example 3
[0085] A mineralized material, the preparation method of which comprises the following steps:
[0086] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0087] (2) 1 L of silk fibroin solution was placed in a high-pressure microfluidizer and circulated for homogenization at 95 MPa for 3 times.
[0088] (3) After the cyclic homogenization treatment is completed, 2 mL of 5 mmol / L vitamin C is added and stirred at 50°C for 45 minutes; then 5 mL of 5 mmol / L hydrogen peroxide is added and oxidative degradation reaction is carried out at 45°C with stirring for 30 minutes to obtain a silk fibroin oligopeptide intermediate solution.
[0089] (4) The supernatant of the silk fibroin oligopeptide intermediate solution is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0090] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0091] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following components in percentage by weight: 5% mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium lauryl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0092] Comparative Example 4
[0093] A mineralized material, the preparation method of which comprises the following steps:
[0094] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0095] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 50°C for 45 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidative degradation reaction was carried out at 45°C with stirring for 30 min to obtain a silk fibroin oligopeptide intermediate solution.
[0096] (3) The concentration of the silk fibroin oligopeptide intermediate solution was adjusted to 100 mg / mL, and the solution was placed in a high-pressure microfluidizer and subjected to cyclic homogenization treatment at 65 MPa for 3 times.
[0097] (4) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0098] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0099] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following components in percentage by weight: 5% mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium lauryl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0100] Comparative Example 5
[0101] A mineralized material, the preparation method of which comprises the following steps:
[0102] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0103] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 50°C for 45 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidative degradation reaction was carried out at 45°C with stirring for 30 min to obtain a silk fibroin oligopeptide intermediate solution.
[0104] (3) The concentration of the silk fibroin oligopeptide intermediate solution was adjusted to 100 mg / mL, and the solution was placed in a high-pressure microfluidizer and subjected to cyclic homogenization treatment at 125 MPa for 3 times.
[0105] (4) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0106] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0107] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following components in percentage by weight: 5% mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium lauryl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0108] Comparative Example 6
[0109] A mineralized material, the preparation method of which comprises the following steps:
[0110] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 3wt% sodium carbonate solution, boil them for 30 minutes, and then soak and wash them with distilled water for 20 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 70°C, 9.0mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:5), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 8000rpm for 20 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a relative molecular mass of 8kDa, and continue to dialyze with ultrapure water for 3 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 15% polyethylene glycol solution for concentration for 24 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 100mg / mL.
[0111] (2) 1 L of silk fibroin solution was added with 2 mL of 5 mmol / L vitamin C and stirred at 50°C for 45 min; then 5 mL of 5 mmol / L hydrogen peroxide was added and oxidative degradation reaction was carried out at 45°C with stirring for 30 min to obtain a silk fibroin oligopeptide intermediate solution.
[0112] (3) The concentration of the silk fibroin oligopeptide intermediate solution was adjusted to 100 mg / mL, and the solution was placed in a high-pressure microfluidizer and subjected to cyclic homogenization treatment at 155 MPa for 3 times.
[0113] (4) The supernatant of the product after the circulation homogenization is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa to remove the macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain the silk fibroin oligopeptide.
[0114] (5) 3 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 7 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 20 mL of 3 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 40° C. for 72 h. After the mineralization reaction, the pH was adjusted to 7.0, and the precipitate was collected by centrifugation. After drying, the precipitate was ultrafinely ground and passed through a 20,000 mesh sieve.
[0115] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following components in percentage by weight: 5% mineralized material, 15% calcium carbonate, 15% sorbitol, 7% glycerol, 3% hydrated silica, 2% saccharin sodium, 2% xanthan gum, 2% sodium lauryl sulfate, 1% cellulose gum, 0.2% paraben, and the balance is water.
[0116] Verification Example 1
[0117] Solubility is the most important functional property of protein oligopeptide. When silk fibroin oligopeptide is treated with high-pressure microfluidization, its particle size becomes smaller, solubility increases, and the corresponding specific surface area increases, which is beneficial to the subsequent mineralization step with hydroxyapatite. In this regard, the silk fibroin oligopeptide samples in Examples 1-3 and Comparative Examples 1-6 were respectively taken for solubility performance testing, and the specific steps are as follows: 0.2g of silk fibroin oligopeptide sample was dissolved in 20mL of deionized water, stirred for 30min, pH was adjusted to neutral, stirred for another 30min, centrifuged at 5000rpm for 10min, and an appropriate amount of supernatant was diluted, and the protein content in the supernatant was determined by the Folin phenol method, with dioctanoic acid (BCA) as the standard protein. Wherein the solubility is calculated according to the following formula:
[0118] Solubility = protein content in supernatant / total protein content in sample × 100%.
[0119] The test results are shown in Table 1 below. The results show that under the conditions of Comparative Examples 1-3, the solubility of silk fibroin oligopeptide is lower than that of Examples 1-3. The silk fibroin oligopeptide treated with high-pressure microfluidization can change the aggregation of oligopeptides, refine the particle size, and significantly improve solubility. In Comparative Example 1, the silk fibroin was not oxidatively degraded, and was directly treated with high-pressure microfluidization, and the solubility was low. The reason is that silk fibroin is a macromolecule, and it is difficult to convert it into silk fibroin oligopeptide without oxidative degradation, and the solubility of macromolecule silk fibroin is poor. Since Comparative Example 2 was not treated with high-pressure microfluidization, its solubility was significantly lower than that of Examples 1-3. In Comparative Example 3, the silk fibroin was first treated with high-pressure microfluidization, and then oxidatively degraded by the silk fibroin oligopeptide, and the solubility was low. The reason is that silk fibroin is a macromolecule, and is limited by the molecular weight of the material. The high-pressure microfluidization treatment has poor processing ability for macromolecules, and it is difficult to evenly disperse and dissolve the macromolecules in water. First oxidative degradation, then high-pressure microfluidization treatment, after the protein can be fully oxidatively degraded into small molecule oligopeptides, high-pressure microfluidization treatment is used to change the refinement of the peptide, so that the oligopeptide molecules are more evenly and delicately dispersed in water, thereby improving solubility. And when the high-pressure microfluidization is treated, the homogenization pressure also has a key influence on the solubility of silk fibroin. Specifically, in Comparative Example 4, under a relatively low homogenization pressure of 65MPa, the silk fibroin oligopeptide has a smaller particle size under the dual effects of shear force and impact force, but its solubility is not high, which is not enough to be well dispersed and dissolved in the water system. When the homogenization pressure is too large and increases to 125MPa (Comparative Example 5) and 155MPa (Comparative Example 6), the solubility of the silk fibroin oligopeptide decreases, which is due to the excessive expansion of the protein molecules in the unfolding process, so that the hydrophobic interaction and electrostatic attraction between molecules are enhanced to produce aggregates, thereby reducing its solubility. It is clear through a large number of studies that when the homogenization pressure reaches 95MPa, the solubility of the silk fibroin oligopeptide is the best.
[0120] Table 1 Solubility of silk fibroin oligopeptide in Examples 1-3 and Comparative Examples 1-6
[0121]
[0122]
[0123] Verification Example 2
[0124] The mineralized materials prepared in Examples 1-3 and Comparative Examples 1-6 were respectively taken to study their effects on the remineralization of tooth enamel.
[0125] The steps of preparing the enamel sample are as follows: fresh bovine teeth are taken, soft tissues are removed, crowns and roots are separated with a hard tissue slicer, the crown surface is polished into a smooth plane with a grinder and polisher, ultrasonic cleaning is performed for 30 minutes, deionized water is rinsed, placed in a 0.9% sodium chloride solution, and stored at 4°C for use. The enamel samples are observed under a microscope, and intact enamel without cracks, caries, or fluoride spots is selected, rinsed with deionized water, and dried, and randomly divided into a negative group (without demineralization treatment), a demineralization group, an embodiment group, and a comparative group.
[0126] The demineralization and remineralization experimental procedures were as follows: all enamel samples were immersed in a demineralization solution (50 mmol / L acetic acid, 2.2 mmol / L potassium dihydrogen phosphate solution, 2.2 mmol / L calcium chloride dihydrate solution, 0.5 mol / L sodium bicarbonate solution, pH 4.5), placed in a 37°C shaker at 100 rpm for demineralization for 72 h, and rinsed with deionized water to form artificial caries.
[0127] The artificially demineralized enamel samples were soaked in the mineralization material solution (concentration of 10 mg / mL) prepared by each group for 20 minutes, rinsed with deionized water, and soaked in an acidic buffer (50 mmol / L acetic acid, 2.25 mmol / L calcium chloride dihydrate solution, 0.5 mol / L sodium bicarbonate solution, 1.5 mmol / L potassium dihydrogen phosphate solution, 130 mmol / L potassium chloride solution, pH 5.0) for 30 minutes, rinsed with deionized water, and dried with filter paper. Finally, they were soaked in a neutral buffer (20 mmol / L HEPES buffer, 2.25 mmol / L calcium chloride dihydrate, 1.5 mmol / L potassium dihydrogen phosphate solution, 130 mmol / L sodium chloride solution, pH 7.0) for 10 minutes, rinsed with deionized water, and dried with filter paper. Repeat 6 times a day for 10 days, and spend the rest of the time in a neutral buffer overnight, and the reagents were changed every day. Remineralization of artificial caries.
[0128] The remineralized enamel samples were embedded and cut longitudinally into thin slices along the center of the fenestration area of the enamel samples under a steady water flow. The slices were 110 μm and stained with 0.1 mmol / L rhodamine B fluorescent dye for 1 h. The excess dye was rinsed with distilled water, dried and sealed with glycerol, and placed under a laser scanning confocal microscope. The samples were scanned at an excitation wavelength of 529 nm and the penetration of rhodamine B was observed under a 10x microscope. The scanned images were processed and analyzed using Image J vl.8.0 software and expressed as total fluorescence. Laser confocal microscopy is an advanced method for observing the demineralization and remineralization of tooth hard tissues. The total fluorescence of the carious area was measured by laser confocal microscopy to understand the demineralization and remineralization of the specimens. Enamel itself cannot fluoresce and needs to be stained with dyes such as rhodamine B. It can emit fluorescence after being irradiated by a laser confocal microscope, and then quantitatively analyzed using Image J software. Fluorescent dye molecules can penetrate into the micropores of demineralized enamel, and the demineralization degree of the demineralized area is proportional to the total fluorescence amount.
[0129] The results are shown in Table 2. The results show that the crystal structures formed in the mineralization process of the samples prepared in Examples 1-3 of the present invention effectively hindered the further penetration of the fluorescent dye molecules into the micropores of the demineralized enamel of the tooth tissue, which indicates that the degree of caries is reduced. This not only confirms the positive role of the examples of the present invention in promoting the remineralization of tooth enamel, but also strongly illustrates its effectiveness and potential as an anti-caries strategy.
[0130] Oxidative degradation of silk fibroin can degrade the macromolecular silk fibroin into small molecular silk fibroin oligopeptides, which is convenient for subsequent mineralization with hydroxyapatite. Comparative Example 1 is inferior to Examples 1-3 in the functional effect of preparing toothpaste with the silk fibroin oligopeptides that have not been oxidatively degraded. Silk fibroin is first oxidatively degraded and then treated with high-pressure microfluidization. The purpose is to first degrade the macromolecular silk fibroin into small molecular silk fibroin oligopeptides. Since the peptide segment has spontaneous aggregation, after being treated with high-pressure microfluidization, the aggregation of the oligopeptides can be changed, and they are more loosely distributed in the solution, which is convenient for subsequent mineralization with hydroxyapatite. If the silk fibroin is first treated with high-pressure microfluidization, the protein particle size is difficult to refine due to its large molecular weight (Comparative Example 3), and the functional effect of preparing toothpaste with it is inferior to Examples 1-3.
[0131] Table 2 Effects of Examples 1-3 and Comparative Examples 1-6 on the Remineralization of Tooth Enamel
[0132]
[0133] Furthermore, a FEI Nova Nano SEM 450 field emission scanning electron microscope was used to characterize the surface element composition of the remineralized enamel, and the calcium-phosphorus ratio was calculated based on the calcium-phosphorus content of the energy spectrum analysis to determine the degree of demineralization. The lower the calcium-phosphorus ratio, the more obvious the demineralization degree, and the more severe the acid erosion of the enamel. The test results are shown in Table 3 below. The results show that after the toothpaste of Examples 1-3 was repaired, the calcium / phosphorus molar ratio of the enamel surface was improved, indicating that the embodiments of the present invention have a repairing effect on the demineralized enamel.
[0134] Table 3 Calcium / phosphorus molar ratio on tooth enamel surface of Examples 1-3 and Comparative Examples 1-6
[0135]
[0136] Verification Example 3
[0137] The toothpastes prepared in Examples 1-3 and Comparative Examples 1-6 were used to study their repairing effects on demineralized chalky plaques on tooth enamel. The specific steps were as follows: 100 subjects were randomly divided into 10 groups, namely a control group (using ordinary toothpaste without hydroxyapatite), an example group and a comparative example group (n=10 in each group). The subjects cleaned their teeth with the example and comparative example toothpastes every morning and evening for 3 months. The inclusion criteria of the subjects were as follows: (1) informed and voluntary participation in this study; (2) clear chalky plaques were visible on the surface of tooth enamel; (3) early enamel caries were determined according to the patient's complaints and imaging examination results.
[0138] The enamel demineralization rate of each group of subjects was tested before treatment and 6 months and 12 months after treatment according to the following formula:
[0139] Enamel demineralization rate = number of demineralized teeth / total number of teeth × 100%.
[0140] The test results are shown in Table 4. The results show that at 6 months and 12 months after treatment, the demineralization rate of the toothpaste prepared using Examples 1-3 of the present invention was significantly lower than that of the control group, indicating that the toothpaste prepared using the process of the examples can effectively inhibit demineralization and promote remineralization.
[0141] Table 4 Comparison of the incidence of demineralization in patients of Examples 1-3 and Comparative Examples 1-6
[0142]
[0143] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a hydroxycellulose-silk fibroin oligopeptide mineralized material based on high-pressure microfluidization technology, characterized in that: The steps include: (1) preparing a silk fibroin solution from silkworm cocoons, and adjusting the silk fibroin concentration to 50-300 mg / mL; (2) adding a reducing agent and continuing the reaction with stirring, and then adding an oxidizing agent to carry out an oxidative degradation reaction under stirring to obtain a silk fibroin oligopeptide intermediate solution; (3) placing the silk fibroin oligopeptide intermediate solution in a high-pressure microfluidizer for cyclic homogenization; (4) ultrafiltration of the product after cyclic homogenization to obtain a silk fibroin oligopeptide solution, and freeze-drying to obtain a silk fibroin oligopeptide; (5) The silk fibroin oligopeptide obtained in step (4) is mixed with hydroxyapatite and dissolved in a saturated calcium nitrate solution, and a sodium phosphate solution is added dropwise under stirring to carry out a mineralization reaction; after the mineralization reaction is completed, the pH is adjusted to neutral, the precipitate is collected by centrifugation, and the precipitate is dried and ultrafinely ground and sieved to obtain the product.
2. The preparation method according to claim 1, characterized in that The reducing agent in step (2) is selected from vitamin C.
3. The preparation method according to claim 1, characterized in that: The oxidant in step (2) is selected from hydrogen peroxide.
4. The preparation method according to claim 1, characterized in that: The stirring reaction in step (2) is carried out at a temperature of 40-60° C. and for a time of 20-60 min.
5. The preparation method according to claim 1, characterized in that: The temperature of the oxidative degradation reaction in step (2) is 30-60° C. and the time is 10-60 min.
6. The preparation method according to claim 1, characterized in that: The pressure of the cyclic homogenization in step (3) is 70-120 MPa, and the number of times is 1-5 times.
7. The preparation method according to claim 1, characterized in that: The ultrafiltration in step (4) is specifically as follows: the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 2 kDa, and the effluent is taken; then the product is separated by an ultrafiltration membrane with a molecular weight of 0.75 kDa, and the retentate is taken to obtain a 0.75-2 kDa silk fibroin oligopeptide solution.
8. The hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the preparation method according to any one of claims 1 to 7 in the preparation of toothpaste.
10. A toothpaste, characterized in that: The invention comprises a hydroxyapatite-silk fibroin oligopeptide mineralized material prepared by the preparation method according to any one of claims 1 to 7, and auxiliary materials.
Citation Information
Patent Citations
Preparation method of peanut nano peptide
CN105533120A
Nnano-emulsion based on silk fibroin as well as preparation method and application thereof
CN110859776A
Preparation method and application of silk fibroin / hydroxyapatite composite micro-nano particle material
CN115054733A
Extraction of silk fibroin powder from broken silkworm cocoon
CN86107142A
Method for producing silk fibroin powder
JP2005281332A